2011
DOI: 10.3109/09553002.2011.595875
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of reduced weightbearing and ionizing radiation on splenic lymphocyte population and function

Abstract: Purpose The effects of radiation +/− hypogravity on immunologic function were investigated using the Partial Weight Suspension (PWS) model (Wagner et al. 2010). Materials and methods Mice were exposed to 0.5, 1, or 2 Gray (Gy) dose of gamma radiation and then placed in the PWS system for 4, 24, 48 hours, or 4 days. Spleens were excised and white blood cells were prepared for flow cytometry analyses. Results The combination of PWS + radiation (1 and 2 Gy doses only) resulted in decreased cell viability at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In contrast, simulated hypogravity brought about by PWS was shown to potentiate splenic lymphocytes to the cell killing effects of radiation (136). A number of other studies indicated that SPE radiation and simulated microgravity produced by HS led to synergistic adverse effects on hematopoietic and immune cell functions, including bacterial containment in the GI tract (152), T-cell activation (136, 138), and death from a bacterial challenge at a sub-lethal dose (151). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, simulated hypogravity brought about by PWS was shown to potentiate splenic lymphocytes to the cell killing effects of radiation (136). A number of other studies indicated that SPE radiation and simulated microgravity produced by HS led to synergistic adverse effects on hematopoietic and immune cell functions, including bacterial containment in the GI tract (152), T-cell activation (136, 138), and death from a bacterial challenge at a sub-lethal dose (151). …”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the impact of hypogravity on the effect of SPE radiation on immunological function, experiments were performed with 6–8 week old female ICR mice that were irradiated with 0.5, 1 or 2 Gy of γ-rays with or without hypogravity simulated using the PWS model, described by Wagner et al (149). The combination treatment with PWS and γ-ray irradiation decreased total splenic lymphocyte viability in a dose dependent manner, and the suppressed splenic lymphocyte viability in groups exposed to a 2 Gy dose of radiation persisted for 4 days, which was the last time point evaluated in the study (136). In addition, the viability of splenic lymphocytes was significantly lower in the mice that received a 1 Gy dose of γ-rays in combination of PWS treatment than in the mice that received a 1 Gy dose of γ-rays without PWS treatment on Day-1 or Day 4 post-irradiation.…”
Section: Acute Radiation Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…As examples, interesting studies on IR effects under MMG or PWS, reported recently, are introduced below. Sanzari et al (2011) investigated the effects of radiation plus/minus hypogravity on immunologic function using the PWS model established by Wagner et al (2010). Mice were exposed to γ -rays with a dose of 0.5, 1, or 2 Gy and were then placed in the PWS system for 4, 24, 48, or 96 h. The combination of PWS plus γ -rays (1 or 2 Gy) resulted in an approximate 20% decrease in cell viability of lymphocytes after 24, 48, or 96 h, compared with those treated with PWS, which itself did not significantly change the level of cell viability.…”
Section: Recent Reports On Influence Of Mmg or Pwsmentioning
confidence: 99%